Interrelations Correlations of Some Sensory – Motor Abilities of Some Fundamental Soccer Goalkeeper Skills in the Soccer University League - Farhan, Ehab Mohammed (Journal of Physical Education, 2022)
The research aimed at identifying the relationship between some sensory – motor abilities and soccer goalkeeper fundamental skills. The researchers used the descriptive method on soccer goalkeepers of the university league 2021 – 2022. Sensory – motor abilities were selected as well as the fundamental skills through expert form. Correlation relationships law was used to find the relationship between sensory – motor abilities and some fundamental soccer skills. The researchers concluded that there is no strong correlation between sensory – motor abilities and some soccer skills due to weakness in some abilities. The researchers recommended that coaches should use exercises and training aids that help develop their sensory – motor abilities during soccer goalkeeper training as well as making periodical tests for sensory motor abilities to evaluate soccer goalkeeper’s level so as to better select training programs that suits them according to different training phases.